RETRACTED: Study of gene expression of Cytokine Genes (TLR-4, NOD-2) in patients with Otitis Media in Al-Najaf Governorate, Iraq - Al-Fatlawi Manar Mohammed Hadi; Al-Ammar Mahdi Hussain; Al-Manssori Yasir Lafta Hassoun (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001